Greener synthesis of 1, 2-butylene carbonate from CO2 using graphene-inorganic nanocomposite catalyst. (15th December 2018) - Onyenkeadi, Victor; Kellici, Suela; Saha, Basudeb
Abstract: The synthesis of 1, 2-butylene carbonate (BC) from cycloaddition reaction of 1, 2-butylene oxide (BO) and carbon dioxide (CO2 ) was investigated using several heterogeneous catalysts in the absence of organic solvent. Continuous hydrothermal flow synthesis (CHFS) has been employed as a rapid and cleaner route for the synthesis of a highly efficient graphene-inorganic heterogeneous catalyst, ceria-lanthana-zirconia/graphene nanocomposite, represented as CeLaZr/GO. The heterogeneous catalysts have been characterised using transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction (XRD) and nitrogen adsorption/desorption (BET for measuring the surface area/pore size distribution). Ceria-lanthana-zirconia/graphene nanocomposite catalyst (CeLaZr/GO) exhibited high catalytic activity as compared to other reported heterogeneous catalysts in the absence of any organic solvent with a selectivity of 76% and 64% yield of 1, 2-butylene carbonate at the reaction conditions of 408 K, 75 bar in 20 h. Highlights: Highly active CeLaZr/GO nanocomposite was successfully prepared using a CHFS reactor. Direct synthesis of BC was catalysed by CeLaZr/GO nanocomposite catalyst. CeLaZr/GO nanocomposite catalyst showed highest catalytic activity. CeLaZr/GO catalyst was reused about 120 h without affecting its performance.